2002
DOI: 10.1152/ajpgi.00446.2001
|View full text |Cite
|
Sign up to set email alerts
|

Micellar distribution of cholesterol and phytosterols after duodenal plant stanol ester infusion

Abstract: Properties of the intestinal digestion of the dietary phytosterols, cholesterol and cholestanol, and the mechanisms by which phytosterols inhibit the intestinal absorption of cholesterol in healthy human subjects are poorly known. We have studied the hydrolysis of dietary plant sterol and stanol esters and their subsequent micellar solubilization by determining their concentrations in micellar and oil phases of the jejunal contents. Two liquid formulas with low (formula 1) and high (formula 2) plant stanol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 38 publications
8
83
0
4
Order By: Relevance
“…The cholesterol lowering by the combination of plant sterols and glucomannan may involve a reduction in both cholesterol absorption and synthesis. Plant sterols have been shown to suppress intestinal cholesterol absorption by reducing dietary and biliary cholesterol incorporation into micelles (Ikeda et al, 1988;Nissinen et al, 2002). However, it has also been shown that the inhibition of the intestinal absorption is partially compensated for by an increase in hepatic cholesterol synthesis rate (Gylling et al, 1999;Jones et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cholesterol lowering by the combination of plant sterols and glucomannan may involve a reduction in both cholesterol absorption and synthesis. Plant sterols have been shown to suppress intestinal cholesterol absorption by reducing dietary and biliary cholesterol incorporation into micelles (Ikeda et al, 1988;Nissinen et al, 2002). However, it has also been shown that the inhibition of the intestinal absorption is partially compensated for by an increase in hepatic cholesterol synthesis rate (Gylling et al, 1999;Jones et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of sterols has now been unquestionably established through many earlier (Weststrate and Meijer, 1998) and recent studies (Hallikainen et al, 2000;Vanstone et al, 2002;Varady et al, 2004). It has been shown that plant sterols lower LDL cholesterol concentrations by inhibiting cholesterol absorption in the intestine (Ikeda et al, 1988;Nissinen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, in other studies with free plant sterols (Weststrate and Meijer, 1998;Hallikainen et al, 1999) or with plant sterol esters (Gylling et al, 1999;Hendriks et al, 1999;Mensink et al, 2002), there has been a significant (8-30%) reduction in b-carotene or a-tocopherol concentrations after lipid adjustment for reduced total or LDL cholesterol. It has been suggested that esterified plant sterols have a greater effect than free plant sterols on the reduction of fat-soluble vitamin absorption because the plant sterol esters partition into the oil phase of the intestine, whereas free sterols partition more frequently into the mixed micellar phase (Nissinen et al, 2002). Details of the regulation of the lipophilic nutrient absorption are largely unknown and this needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The only well-documented hypocholesterolemic mechanism of action of plant sterols/stanols is that when present in large enough quantities in the upper small intestine, they displace cholesterol from the mixed micelles so that cholesterol absorption is partially inhibited [3,4]. But how much dietary plant sterols/stanols are needed?…”
Section: Plant Sterols/stanols In Foodmentioning
confidence: 99%